Design of Shredding System in Recycle Vending Machine - Azhar, Nor Ainaa; ABD RAHIM, ABD KHALIL (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The design of the shredding system in recycle vending machine is used to shred paper, plastic bottles, and cans. By integrating this shredding system, the materials can be crushed into smaller pieces, thereby optimizing storage space for each form of material and it has proven to be an effective solution for reducing the size of paper, plastic bottles, and cans. This innovation aims to assist university students in minimizing plastic waste generation, specifically by enabling them to conveniently dispose of cans, bottles, and paper waste in recycle vending machines. To develop a comprehensive shredding system, a unified shredding machine design was created for paper, plastic bottles, and cans, incorporating a wall separation mechanism to segregate the materials during the shredding process. The design process involved employing SolidWorks for 3D modeling and conducting calculations and simulation analyses to validate the design’s efficacy. The design and simulation results confirm the feasibility and efficiency of the shredding process. This study presents a concise summary of the proposed shredding system, highlighting its potential impact on waste reduction in university settings. Implementation of this system in recycling vending machines can contribute significantly to the overall reduction of plastic waste, benefiting both the environment and the university community.